Promotion of beekeeping: Insights from an empirical analysis of three honey value chains in Benin - DOSSOU, Smith A. R.; ADANGUIDI, JEAN; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; Gbedomon, Castro Rodrigue (My University, 2021)
Beekeeping is increasingly promoted in developing countries as a promising option for income diversification in rural areas while contributing to poverty alleviation. Unfortunately, the development of the value chains of its most known and marketed product (honey) is still in its beginning stages. Little is known about the honey value chain environment and entry points for its development. Through interviews with 406 informants, this study investigated three honey value chains – “honey harvested in wild,” “honey from traditional beekeeping” and “honey from semimodern beekeeping.” Data was collected on their operation, profitability, and long-term perspectives. The following agents were involved in the value chains: input suppliers, honey producers, middlemen, transporters, and consumers. Farmer's associations, government, non-governmental organizations, quality control organizations, and financial organizations were also involved in the operation of the value chain of honey from semi-modern beekeeping. In the case of the value chains of honey harvested in the wild and honey from traditional beekeeping, only a government department and financial organizations were involved in its operation. Networks were the main coordination mechanism in the value chain of honey from semi-modern beekeeping. There was a low representativeness of market coordination in the three value chains. The value chain of honey from semi-modern beekeeping had the highest value-added. All of the value chains were financially profitable, but various weaknesses prevented the efficiency of the value chains. Relevant policy options are discussed to address these issues.
Keywords: Benin; governance; honey production; institutional environment; performance; Value chains